2015
DOI: 10.21608/eajbsa.2015.12883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Coloured Light Traps on Captures and Controlling Wax Moth (Lepidoptera: Pyralidae).

Abstract: Coloured light trap Achroia grisella Fab Field experiments were conducted to determine the attractive action of different colours (red, yellow, green, blue, white and black) to adult greater ,Galleria mellonella L. and lesser, Achroia grisella Fab., (Lepidoptera: Pyralidae) and to assess the influence of trap colour on their capture moths in plastic bottles baited traps. The results demonstrated, Galleria mellonella L. and Achroia grisella Fab. can distinguish between various colours , with regard to treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies that have demonstrated colour preferences in moths are common. Some species prefer yellow, green and/or orange (Knight & Miliczky, 2003; Singh & Saxena, 2004; Karalius & Bûda, 2007; Roubos & Liburd, 2008), whereas others show preference for other colours (Taha et al ., 2012; Mabrouk & Mahbob, 2015) or no preference (Clare et al ., 2000; Bloem et al ., 2005; Haynes et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have demonstrated colour preferences in moths are common. Some species prefer yellow, green and/or orange (Knight & Miliczky, 2003; Singh & Saxena, 2004; Karalius & Bûda, 2007; Roubos & Liburd, 2008), whereas others show preference for other colours (Taha et al ., 2012; Mabrouk & Mahbob, 2015) or no preference (Clare et al ., 2000; Bloem et al ., 2005; Haynes et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%